2022
DOI: 10.1142/s0218495822500121
|View full text |Cite
|
Sign up to set email alerts
|

Women Entrepreneurs in Saudi Arabia: A Portrait of Progress in the Context of Their Drivers and Inhibitors

Abstract: This study explores the barriers and challenges faced by Saudi women entrepreneurs along with the motivational forces that drives them towards entrepreneurship. This study employs a qualitative research design, and is based on the interview of 11 Saudi women entrepreneurs and includes a review of data on the motivational factors and challenges faced by them using interpretative phenomenological analysis. Research participants’ perspectives have been quoted for each distinct theme that emerged from the intervie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 38 publications
1
7
0
1
Order By: Relevance
“…Thus, the participants further clarified that when males neglect them, this is one problem, but the ignorance or fear expressed by female peers was a bigger issue as they often lacked the simple support of a female colleague. This finding confirms previous research that women’s underrepresentation in leadership positions is not due to women’s lack of desire to grow, but rather, compared to men, women are less optimistic due to interpersonal factors and less support from colleagues [ 23 ].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Thus, the participants further clarified that when males neglect them, this is one problem, but the ignorance or fear expressed by female peers was a bigger issue as they often lacked the simple support of a female colleague. This finding confirms previous research that women’s underrepresentation in leadership positions is not due to women’s lack of desire to grow, but rather, compared to men, women are less optimistic due to interpersonal factors and less support from colleagues [ 23 ].…”
Section: Discussionsupporting
confidence: 90%
“…According to earlier research, women in medicine face the same challenges in advancing to leadership positions as other colleagues [ 21 23 ]. This study found that some women face prejudices that equate leadership with masculinity, preventing them from taking on higher positions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Theoretically, this study also utilizes the distinction between the country image and destination image of developing countries made by earlier studies [124][125][126] in order to link the tourist's experience in developing countries more closely to the destination than the country. This allows a developing nation to have favorable perception of its particular tourism locations when it comes to the quality of the visitors' experiences, regardless of what opinions the tourists may have of the nation as a whole.…”
Section: Theoretical Implicationsmentioning
confidence: 99%
“…Beberapa penelitian yang telah dilakukan seperti penelitian Adami & Mostaghi (2020) yang menggunakan pendekatan analitis, deskriptif, dan historis berdasarkan reformasi dalam negeri dan Visi 2030 untuk menyimpulkan bahwa kebijakan regional Arab Saudi berasal dari upaya Riyadh untuk kembali ke situasi sebelum tahun 2011, bukan dari revisionisme Saudi. Alreshoodi, et al (2022) menulis bahwa faktor-faktor yang memotivasi perempuan Arab Saudi dalam berwirausaha antara lain adalah hasrat, peluang, ketidakpuasan dan dukungan keluarga. Selain itu, penelitian Winarni & Permana (2022) yang menyatakan bahwa norma, reputasi Arab Saudi, sosial dan budaya politik, dan citra Muhammad bin Salma yang menjadi penghambat konstruksi identitas Arab Saudi.…”
Section: Pendahuluanunclassified